An exploration of knowledge, risk perceptions, and communication in a family with multiple genetic risks for Parkinson's disease - Daykin, Emily C.; Poffenberger, Chelsie N.; Do, Jenny; Ryan, Emory; Tayebi, Nahid; Sidransky, Ellen; Lopez, Grisel; Hadley, Donald W. (Journal of genetic counseling, 2023)
Genomic testing increasingly challenges health care providers and patients to understand, share, and use information. The provision of polygenic risks is anticipated to complicate comprehension, communication, and risk perception further. This manuscript aims to illuminate the challenges confronting families with multiple genetic risks for Parkinson's disease. Identifying and planning for such issues may prove valuable to family members now and in the future, should neuroprotective or genotype‐specific therapies become available. We present qualitative data from interviews with a multi‐generational family carrying pathogenic variants in the glucocerebrosidase (GBA1) and leucine‐rich repeat kinase 2 (LRRK2) genes which are associated with an increased risk for developing Parkinson's disease (PD). The family includes two brothers (heterozygous for LRRK2 p.G2019S and homozygous for GBA1 p.N409S) and their four descendants. The brothers were concordant for GD and discordant for PD. Genetic counseling and testing were provided to four of the six participants. Two years later, semi‐structured interviews were conducted with the initial participants (n = 4) and two additional first‐degree relatives. Interviews were transcribed and thematically analyzed, providing the basis for this report. Illuminated topics include the perceived risk of developing PD, recall of genetic information, and family communication. With the expanding use of exome and genome sequencing, we anticipate that genetic counselors will increasingly face the challenges demonstrated by this case involving multiple genetic risks for PD, limited data to clarify risk, and the inherent variability of family communication, genetic knowledge, and risk perception. This clinical case report provides a compelling narrative demonstrating the need for additional research exploring these multifaceted topics relevant to both families facing these challenges and providers striving to assist, support and guide their journey.